The nexus between migration and environmental degradation based on fundamental climate variables and extreme climate indices for the MENA domain - Nazan An; Zekican Demiralay; Meltem Ucal; M. Levent Kurnaz (Climate Services)
Environmental migration has recently become primary source of population growth and environmental degradation from extreme events has created the environmental refugee concept with a variety of manners affecting lives. For understanding of the environmental degradation impact on migration, a hybrid approach (regional climate modelling, RegCM4.4 and statistical modelling, ordered logit) has been applied for 65 countries in the Middle East and North Africa (MENA) for the periods of 2021–2050 and 2051–2080. It is aimed to examine how climate change affect migration by applying fundamental climate variables (i.e., maximum temperature, minimum temperature, and precipitation) and the control variables (i.e., the hot days, the tropical nights, and the dry days) in the MENA. While key findings indicate an increase in the minimum temperatures (Tmin) in future in all populous cities, the water amount may further decrease in the mid-latitude and Mediterranean with temperate climates due to precipitation change. While it may pose a high risk in the regions having experienced extreme temperatures e.g., tropical nights (Tn), it may further adversely affect ones not having experienced extremes. Considering statistically significant positive relationship between Tmin, and net migration rate (NMIG), and negative relationship between precipitation and NMIG, it may encourage migration to cooler regions.